Public Service vs State Service in the Field of Healthcare: Legal and Terminological Issues in Ukraine and Internationally - Muzyka-Stefanchuk, O.; Stefanchuk, M.; Muzyka, L.; Anishchenko, M. A.; Аніщенко, Михайло Анатолійович (My University, 2024)
The problem of optimal organization and effective exercise of public authority is directly related to the preservation of the state in general, with its efficient adaptation in the context of interstate integration. After all, public authority accompanies all social processes in society, manages the affairs of the state, realizes its tasks and goals - serving the people as the only source of power, and contributes to the formation of a legal, democratic, social state.